Simulation and Sustainability Assessment Of H2S Utilization from Acid Gas on Haldor Topse Wet Gas Sulfuric Acid and Claus - Sitisaro Binawae; Zulfan Adi Putra (Journal of Applied Materials and Technology, 2021)
Claus process is a widely adopted process to reduce emissions from refineries by converting H2S into elemental sulfur. On the other hand, Haldor Topsoe’s Wet Gas Sulfuric Acid (WSA) is an alternative to convert H2S directly into sulfuric acid. The purpose of this project was to simulate both of these state-of-the-art technologies and evaluate their suitability for various acid gas capacity and H2S concentrations. Three sustainability pillars of people (safety), planet (environment), and profit were used as the comparison metrics. The developed simulation (1st principle) models were used to generate lots of data as the basis for subsequent development of regression models. The latter models were used in the comparisons for they are much faster in calculations than the 1st principle models. The results showed that the WSA process was safer (lower Fire and Explosion Damage Index), more environmentally friendly (lower Global Warming Potential), and more profitable (higher annual profit) in most of the evaluated operating conditions.